A path analysis study of factors influencing hospital staff perceptions of quality of care factors associated with patient satisfaction and patient experience - Sandra G. Leggat; Leila Karimi; Timothy Bartram (BMC, 2017)
Abstract Background Hospital staff are interested in information on patient satisfaction and patient experience that can help them improve quality of care. Staff perceptions of quality of care have been identified as useful proxies when patient data are not available. This study explores the organizational factors and staff attitudes that influence staff perceptions of the quality of the care they provide in relation to patient satisfaction and patient experience. Methods Cross sectional survey completed by 258 staff of a large multi-campus, integrated metropolitan hospital in Australia. Structured equation modelling was used to analyse the data. Results Our data suggest that different perceived organizational factors and staff attitudes contribute to different pathways for patient satisfaction and patient experience indicators. Hospital staff in our sample were more likely to indicate they provided the care that would result in higher patient satisfaction if they felt empowered within a psychologically safe environment. Conversely their views on patient experience were related to their commitment towards their hospital. There was no relationship between the staff perceptions of patient satisfaction and the staff response to the friends and family test. Conclusions This study provides empirical evidence that staff perceptions of the quality of care they provide that is seen to be related to patient satisfaction and patient experience are enacted through different pathways that reflect differing perceptions of organizational factors and workplace psychological attitudes.